The Effects of Bicycle Simulator Training on Anticipatory and Compensatory Postural Control in Older Adults: Study Protocol for a Single-Blind Randomized Controlled Trial - Batcir, Shani; Lubovsky, Omri; Bachner, Yaacov G.; Melzer, Itshak (Frontiers in Neurology, 2021)
Background: Falls are the leading cause of fatal and non-fatal injuries among older adults. Perturbation-Based-Balance Training (PBBT) is a promising approach to reduce fall rates by improving reactive balance responses. PBBT programs are designed for older adults who are able to stand and walk on a motorized treadmill independently. However, frail older adults, whose fall rates are higher, may not have this ability and they cannot participate. Thus, there is a critical need for innovative perturbation exercise programs to improve reactive balance and reduce the fall risks among older adults in a wider range of functioning. Trunk and arms are highly involved in reactive balance reactions. We aim to investigate whether an alternative PBBT program that provides perturbations during hands-free bicycling in a sitting position, geared to improve trunk and arm reactive responses, can be transferred to reduce fall risks and improve balance function among pre-frail older adults. Methods: In a single-blinded randomized-controlled trial, 68 community-dwelling pre-frail older adults are randomly allocated into two intervention groups. The experimental group receives 24-PBBT sessions over 12-weeks that include self-induced internal and machine-induced external unannounced perturbations of balance during hands-free pedaling on a bicycle-simulator system, in combination with cognitive dual-tasks. The control group receives 24 pedaling sessions over 12-weeks by the same bicycle-simulator system under the same cognitive dual-tasks, but without balance perturbations. Participants' reactive and proactive balance functions and gait function are assessed before and after the 12-week intervention period (e.g., balance reactive responses and strategies, voluntary step execution test, postural stability in upright standing, Berg Balance Test, Six-meter walk test, as well as late life function and fear of falling questionnaires). Discussion: This research addresses two key issues in relation to balance re-training: 1) generalization of balance skills acquired through exposure to postural perturbations in a sitting position investigating the ability of pre-frail older adults to improve reactive and proactive balance responses in standing and walking, and 2) the individualization of perturbation training to older adults’ neuromotor capacities in order to optimize training responses and their applicability to real-life challenges.